Empowered Students in Era 5.0 Through Digital Preneurship - Hayati, Sri Nur; Sumiati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
Era 5.0 is marked by deeper integration between technology and human life, with digitalization becoming the backbone of various aspects of life, including education and business. In this context, students are required to have relevant skills and knowledge in facing the challenges and opportunities offered. One of the crucial skills is digital entrepreneurship. This skill combines entrepreneurial concepts with digital technology to create and manage a business. However, the level of digital literacy in Indonesia is still low, only 62%, compared to the ASEAN average of 70%. Therefore, to overcome this problem, this research was carried out with the aim of evaluating the effectiveness of digital preneurship webinars in increasing student knowledge, skills, attitudes and motivation. The experimental method was used involving 47 students as participants. Pretest and posttest data were processed using the normality test and paired T test. The research results show that the pretest and posttest data are normally distributed, and there is a significant difference between the pretest and posttest results with the Sig value. 0.000 < 0.05. In conclusion, webinars are effective in increasing participants' knowledge about digital entrepreneurship. Era 5.0 ditandai dengan integrasi yang lebih dalam antara teknologi dan kehidupan manusia dengan digitalisasi menjadi tulang punggung pada berbagai aspek kehidupan, termasuk pendidikan dan bisnis. Dalam konteks ini, mahasiswa dituntut untuk memiliki keterampilan dan pengetahuan yang relevan dalam menghadapi tantangan dan peluang yang ditawarkan. Salah satu keterampilan yang krusial adalah digital preneurship. Keterampilan ini menggabungkan konsep kewirausahaan dengan teknologi digital guna menciptakan dan mengelola bisnis. Namun, tingkat literasi digital di Indonesia masih rendah, hanya sebesar 62%, dibandingkan dengan rata-rata ASEAN sebesar 70%. Oleh karena itu untuk mengatasi masalah maka dilakukanlah penelitian ini dengan tujuan untuk mengevaluasi efektivitas webinar digital preneurship dalam meningkatkan pengetahuan, keterampilan, sikap, dan motivasi mahasiswa. Metode eksperimen digunakan dengan melibatkan 47 mahasiswa sebagai peserta. Data pretest dan posttest diolah menggunakan uji normalitas dan uji T berpasangan. Hasil penelitian menunjukkan bahwa data pretest dan posttest berdistribusi normal, dan terdapat perbedaan signifikan antara hasil pretest dan posttest dengan nilai Sig. 0.000 < 0.05. Kesimpulannya, webinar efektif dalam meningkatkan pengetahuan peserta tentang digital preneurship.